Wine spirit ageing with chestnut staves under different micro-oxygenation strategies: effects on the volatile compounds and sensory profile - Caldeira, Ilda (2021)
The purpose of this work is to evaluate the wine spirit aged by an alternative process (staves combined with different micro-oxygenation levels) and its comparison with the traditional process (wooden barrels). This evaluation was made by analyzing the volatile compounds and sensory profile of the spirits during 365 days of ageing. The findings confirmed the role played by oxygen in the volatile profile of aged wine spirits. Samples of alternative ageing modalities were well distinguished from those of wooden barrels based on the volatile profile, namely on the concentrations of several volatile phenols. From a sensory point of view, the results are promising with high overall consistency scores obtained from samples of alternative ageing process modalities